Community building in the Shepherd of Hermas : a critical study of some key aspects - Grundeken, Mark, 1984- (Vigiliae Christianae, Supplements, 2015)
In Community Building in the Shepherd of Hermas , Mark Grundeken investigates key aspects of Christian community life as reflected upon in the early Christian writing the Shepherd of Hermas (2nd century C.E.). Grundeken's thematic study deals with various topics: the community's identity, including its (alleged) 'Jewish Christianness', (lack of) resurrection belief, sectarian tendencies and its relation to the authorities and to the emperor cult; social features, encompassing gender roles and charity; and rituals such as baptism, metanoia , Eucharistic meals, the Sunday collection, dancing (and singing), the 'holy kiss' and reading of Scripture. The many fruitful entries prove Hermas to be one of the main texts for studying the development of community building in the early church.